The Effect of Incorporation of 0.5 %wt. Silica Nanoparticles on the Micro Shear Bond Strength of a Resin Modified Glass Ionomer Cement - Rezvani, Mohammad Bagher (J Dent (Shiraz), 2019)
STATEMENT OF THE PROBLEM: The clinical success of glass ionomer restorations depends on the strength of resin-modified glass ionomer (RMGI) cement bonding to dentin and there is limited information available regarding the bond strength of resin modified glass ionomers containing silica nanoparticles to dental structures. PURPOSE: The aim of this study was to compare the microshear bond strength (µSBS) of RMGI with and without silica (SiO2) nanoparticles to dentin of permanent teeth. MATERIALS AND METHOD: In this experimental study, the occlusal surfaces of 30 freshly extracted intact third molars were ground to expose the flat dentin and after conditioning with 20% poly acrylic acid, were randomly assigned to two main groups (n=15). The first group was filled with RMGI (Fuji II LC, GC) and the second group was filled with RMGI plus 0.5%wt. silica nanoparticles. Then, each main group was divided into three subgroups, and then stored in an incubator at 37 oC with 100% humidity for 1, 7, and 30 days. The µSBS test was performed using a universal testing machine (1 mm/min). The data were analyzed by t-test, repeated measures ANOVA and Tukey test (p< 0.05). RESULTS: There were no statistically significant differences between the mean µSBS of the groups with and without nanoparticles along the different storage periods (p> 0.05). There was significant difference in µSBS values among the three different storage periods in all the tested materials (p< 0.05). CONCLUSION: Incorporation of 0.5 %wt. silica nanoparticles did not compromise the µSBS of Fuji II LC RMGI to dentin.